Analisis Visual Pesan Dakwah dalam Kaligrafi Kontemporer di Instagram - Nuha, Achmad Arifulin; Sholeh, Moh. (Dakwah, 2024)
This study analyzes how contemporary calligraphy is used as a medium for Islamic preaching (dakwah) by Refil Andriansyah through the Instagram platform. Utilizing a qualitative approach with Charles Sanders Peirce's semiotic theory, this research examines the visual signs in Refil's works to understand the meanings embedded within them. The findings show that contemporary calligraphy not only serves as an aesthetic art form but also as an effective medium for spiritual communication. Symbols such as the "Allah" inscription and minaret icons in Refil's works convey profound moral and religious messages, making them a powerful tool for dakwah. Instagram, as a visual platform, allows these works to reach a broad and diverse audience, especially the younger generation active on social media. This study concludes that contemporary calligraphy supported by digital technology has great potential to become a relevant and inclusive tool for dakwah in the modern era. Traditional Islamic calligraphy, when combined with contemporary elements and disseminated through social media, can remain vibrant and dynamic, making a significant impact in spreading religious messages to a wider audience.